Strategy and outcome statements in academic and nonacademic orthopaedic surgery institutions. Issue 1 (January 2017) - Job, Alan; Glezos, Christopher D.; Sharan, Alok
Abstract : Background: As the United States healthcare system transitions to a value-based system, it is becoming increasingly important for health care providers and institutions to maintain a strategy that allows them to remain competitive and meet patient demands. The purpose of this study was to compare the number of academic orthopaedic surgery institutions to nonacademic orthopaedic surgery institutions that publish their strategy statements online. As delivering superior patient outcomes is critical for a successful strategy in a value-based system, the study also aims to compare the rates of published outcome scores on the websites of the two groups. It was hypothesized that nonacademic institutions would have greater rates of strategic statements and outcome scores that are published online compared to academic institutions. Methods: The websites of all 149 academic orthopaedic institutions in the United Stated and the top 21 U.S. News ranked nonacademic orthopaedic surgery institutions were evaluated for predetermined categories of strategy and outcome scores. Results: It was found that 95% of nonacademic institutions had strategic statements compared to only 38% of academic institutions. Similarly 30% of nonacademic institutions presented a patient outcome score on their website compared to only 14.3% of academic institutions. Conclusions: It is clear that nonacademic orthopaedic institutions are competing with strategies focused on components of value-based care and positive patient outcomes in order to attract the patient population.